The Influence of Financial Performance on Stock Prices in Banking Companies Listed on The Indonesia Stock Exchange - Harisda; Yusuf , Syarifuddin; Syukri, Fitriyani (PT. Maju Malaqbi Makkarana, 2025)
Stock price fluctuations in banking companies listed on the Indonesia Stock Exchange (IDX) reflect the financial condition of the company and are a major concern for both companies and investors. One of the factors that influences stock prices is the company's financial performance. This study aims to examine the effect of ROA and EPS on stock prices, both partially and simultaneously. This study uses a quantitative approach with secondary data in the form of annual financial reports of the population of all banking companies listed on the IDX for the period 2020–2023. The research sample was selected using a purposive sampling technique, resulting in 13 companies with a total of 52 data. Data analysis used multiple linear regression after going through the classical assumption test to ensure the feasibility of the model. The results of the study showed that partially, Return on Assets (ROA) did not have a significant effect on stock prices. This is thought to be due to the instability of external factors and market expectations that are not fully focused on the efficiency of asset use. Conversely, Earnings Per Share (EPS) has a positive and significant effect on stock prices, indicating that investors tend to prioritize earnings per share as the main indicator in assessing a company's prospects. This finding confirms that in the context of banking companies in Indonesia, EPS is more important than ROA in making investment decisions